2018
DOI: 10.1016/j.jmbbm.2017.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH and application time of meta-phosphoric acid on resin-enamel and resin-dentin bonding

Abstract: The use of 40% meta-phosphoric acid with a pH of 0.5 is an alternative acid-etching agent for dentin and enamel bonding. Furthermore, the use of MPA preserves the resin-dentin interface over a 6-months period, due to presence of brushite and octacalcium phosphate and a reduced demineralization pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…For dentin bonding, the dentin’s collagen fibers provide the main source of bonding force, and the reduced long-term bond durability caused by collagen degradation is the main problem of dentin bonding. 40 Therefore, the activation of metalloproteinases in dentin and the subsequent degradation of collagen or hybrid layer is the main index for evaluation the bonding durability of dentin, which makes long-term water storage a valuable artificial aging technique. 41 Enamel comprises up to 96% inorganic substances; therefore, thermal stress might induce much greater damage around an adhesive layer on enamel than hydrolytic degradation, and thermocycling is thus recommended to simulate in vivo aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dentin bonding, the dentin’s collagen fibers provide the main source of bonding force, and the reduced long-term bond durability caused by collagen degradation is the main problem of dentin bonding. 40 Therefore, the activation of metalloproteinases in dentin and the subsequent degradation of collagen or hybrid layer is the main index for evaluation the bonding durability of dentin, which makes long-term water storage a valuable artificial aging technique. 41 Enamel comprises up to 96% inorganic substances; therefore, thermal stress might induce much greater damage around an adhesive layer on enamel than hydrolytic degradation, and thermocycling is thus recommended to simulate in vivo aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, the main cause of clinical failure of restorations is loss of adhesion and/or destruction of edge seal; therefore, the durability of the material is a more important indicator of bonding performance. For dentin bonding, the dentin’s collagen fibers provide the main source of bonding force, and the reduced long-term bond durability caused by collagen degradation is the main problem of dentin bonding . Therefore, the activation of metalloproteinases in dentin and the subsequent degradation of collagen or hybrid layer is the main index for evaluation the bonding durability of dentin, which makes long-term water storage a valuable artificial aging technique .…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of enamel erosion and remineralization of enamel through orthodontic treatment is a crucial issue. [ 2 3 4 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…(4) Application time It seems the same bonding value between 5 and 37% phosphoric acid etching in the range of 15 s to 1 min. It proves good tolerance of enamel etching with different prosthesis (Cardenas et al, 2018;Sai et al, 2018).…”
Section: Adhesion To Enamelmentioning
confidence: 63%
“…(3) Consistency A study showed that gels are as effective as liquid solutions. Therefore, we prefer colored gels that allow precise operation and good visual control (Cardenas et al, 2018).…”
Section: Adhesion To Enamelmentioning
confidence: 99%